2019
DOI: 10.1002/pssb.201900561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wafer Off‐Angles on Defect Formation in Drift Layers Grown on Free‐Standing GaN Substrates

Abstract: The effect of the surface off‐angle toward either the a‐ or m‐axis on the defect formation is characterized using deep‐level transient spectroscopy (DLTS) in conjunction with the carrier concentration for Ni Schottky contacts formed on n‐GaN drift layers. In both noncontact and conventional capacitance–voltage results, off‐angle dependence on carrier concentration is observed. For all samples, a large dominant peak appears at approximately 270 K in the DLTS spectra and is attributed to E3 (EC − 0.57–0.61 eV) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In many studies, the E3 level has been associated with nitrogen antisites (N Ga ), 11,[14][15][16] although the possibility that impurities are responsible has also been discussed. Several groups have proposed that the origin of this level is related to carbon (C) [17][18][19] or magnesium (Mg) 20,21) impurities, although iron (Fe) is also a possibility. Fe is a well-known dopant for semiinsulating GaN, and the properties of Fe-doped GaN have been investigated in detail.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, the E3 level has been associated with nitrogen antisites (N Ga ), 11,[14][15][16] although the possibility that impurities are responsible has also been discussed. Several groups have proposed that the origin of this level is related to carbon (C) [17][18][19] or magnesium (Mg) 20,21) impurities, although iron (Fe) is also a possibility. Fe is a well-known dopant for semiinsulating GaN, and the properties of Fe-doped GaN have been investigated in detail.…”
mentioning
confidence: 99%
“…The wide range of theories regarding the origin of E3 traps can be attributed to several factors. Firstly, E3 traps have been observed even in GaN layers not intentionally doped with Fe, [11][12][13][14][15][16][17][18][19][20][21] although the Fe concentrations were not always assessed. Secondly, E3 traps have been identified in both heteroepitaxial GaN grown on sapphire [11][12][13][14][15][16][17][18]21,22) and homoepitaxial GaN grown on freestanding GaN, 16,28,29) which makes it difficult to ascertain the relationship between E3 traps and threading dislocations (TDs).…”
mentioning
confidence: 99%
“…Several studies of MOCVD GaN homoepitaxy have shown low carbon concentrations at mid‐ to low‐10 15 cm −3 according to secondary ion mass spectroscopy (SIMS). [ 24–27 ] Despite tremendous efforts on suppressing C incorporation by tuning growth conditions, such as V/III ratio, growth temperature, and growth pressure, [ 22,24,28–30 ] lowering C concentration while maintaining a fast growth rate remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…2,3) For the performance improvement of such devices, it is necessary to reduce the carbon impurity, which is known to create deep levels. [4][5][6][7][8][9] In the case of green laser diodes, for example, the growth temperature T g for p-type (Al)GaN layers has to be low (about 900 °C) to avoid thermal degradation of high-Incontent InGaN/GaN multi-quantum wells. 10) Such low T g during metalorganic vapor-phase epitaxy (MOVPE) induces severe carbon incorporation, resulting in high-resistivity p-(Al)GaN.…”
mentioning
confidence: 99%